Determination and modelling of evapotranspiration of bearing and non-bearing apple trees at Grabouw in the Western Cape - Meyer, Aline (Stellenbosch : Stellenbosch University, 2024)
Thesis (PhDAgric)--Stellenbosch University, 2024.